(untitled) (Research, Society and Development, 2023)
The sexually transmitted infections (STIs) are caused by more than 30 etiological agents, they can be: viruses, bacteria, fungi and protozoa, transmitted mainly through sexual contact and, eventually, through blood. Among these diseases, one of the most common is syphilis, which is systemic, curable and exclusive to humans. Objective: To describe the perceptions of nurses in relation to the treatment of gestational syphilis in a health district (DS) in the city of Curitiba/PR. Method: The method had a qualitative approach with a descriptive character, in which semi-structured interviews were carried out with 15 nurses from the Health Care Network (RAS) in a Sanitary District (DS) in Curitiba/PR, later these were transcribed and grouped in a spreadsheet from Microsoft Excel to the start of Minayo’s content analysis, Results: The analysis resulted in four categories highlighted as: lack of adherence to treatment; difficulties encountered in carrying out the protocol; lack of scientific knowledge about a pathology; and carrying out training for professional nurses in the treatment of syphilis during pregnancy. Final considerations: It was evidenced the need to approach with strategies in permanent education in health, to go beyond constant updates, but also to promote reflections and debates about the problems raised by the professionals themselves. Among them, the most perceived challenges were insecurity and high demand in the daily routine of nurses, or that prevented the performance of specific protocols for the category, including the treatment of gestational syphilis.